2017
DOI: 10.1007/s11121-017-0853-6
|View full text |Cite
|
Sign up to set email alerts
|

For Whom Do Parenting Interventions to Prevent Adolescent Substance Use Work?

Abstract: Adolescent substance use continues to be a significant public health problem. Parent training interventions are effective preventive strategies to reduce youth substance use. However, little is known about differences in effectiveness for youth across demographic characteristics. This review assessed the effectiveness of parent training programs at reducing adolescent substance use by participant gender, age, and race/ethnicity. Pubmed/MEDLINE, ERIC, CINAHL, and PsycINFO were searched from database origin to O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…To date, approaches to substance use prevention have traditionally focused on adolescents themselves, despite evidence suggesting that parents play a critical role in substance use initiation [ 10 - 13 ]. The CSP study addresses the need for an integrated program for both students and their parents that is potentially sustainable through internet-based facilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, approaches to substance use prevention have traditionally focused on adolescents themselves, despite evidence suggesting that parents play a critical role in substance use initiation [ 10 - 13 ]. The CSP study addresses the need for an integrated program for both students and their parents that is potentially sustainable through internet-based facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional approaches to substance use prevention have focused on adolescents only; however, recent evidence suggests that expanding student interventions to include parenting components could markedly increase prevention effects [ 6 - 8 ]. This is because parents are key agents of adolescent socialization, especially in the initiation and development of substance use [ 9 - 13 ], and parenting interventions have been identified as critical components of effective substance use prevention programs [ 6 , 9 , 13 , 14 ]. Moreover, adolescent substance use is an area of substantial concern for parents, who generally want to be engaged in substance use harm prevention [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, especially with interventions taking on newer problems, it is not evident what the key moderators will be. Accordingly, evaluators could suggest moderators common in other evaluation studies, including demographic characteristics such as gender, age, ethnicity/race, sexual orientation, education, and income, as factors that may produce differential intervention effects (Garcia‐Huidobro, Doty, Davis, Borowsky, & Allen, ). Examples of other potential moderators include mental health, family structure, and adverse childhood experiences.…”
Section: Fle Program Evaluation Best Practicesmentioning
confidence: 99%
“…Cultural adaptation research has grown dramatically in recent years. Meta-analyses and systematic reviews have demonstrated the effectiveness of culturally adapted EBIs with minority populations (Baumann et al, 2015;Garcia-Huidobro, Doty, Davis, Borowsky, & Allen, 2018). For example, Hall, Ibaraki, Huang, Marti, and Stice (2016) found that culturally adapted psychological interventions had 4.68 times greater odds of producing remission than nonadapted conditions.…”
Section: Developments In Cultural Adaptationmentioning
confidence: 99%